Infrastructure Development and Property Values in Low Income Residential Properties in Bulawayo - Average chigwenya; Desire Dube (Department of Architecture Universitas Muhammadiyah Jakarta, 2018)
There is a usual positive correlation between infrastructure development and property values. However, in Bulawayo, this correlation does not usually follow in all aspects of properties transactions. This research seeks to find out trends in infrastructure development and property values in the city of Bulawayo. This research took a mixed methods approach in data collection; both qualitative and quantitative methods were utilized. Questionnaires were administered to people in low-income areas of Pumula, Cowdrey Park and Emganwini. In-depth interviews with key informants in the real estate sector were done to cross-fertilize and enrich the inquiry. This research found out that in most cases there is a strong correlation between infrastructure development and property values, but in some cases, there is not any correlation as some forces are put in play distorting the market play. This research also discovered that apart from infrastructure, property values in Bulawayo’s low-income residential suburbs are also affected by income, supply, and demand factors.